(untitled) (Journal of Tikapur Multiple Campus, 2023)
With the development of information technology, today’s scholars can store references in their library and use it to format citations in academic writing. This phenomenological paper describes how I modified the Endnote X9 reference types and the APA 7th output style; and how I entered the components of citation into the fields for each of the basic reference types in the reference window of the Endnote library to create accurate in-text and end-text citations focusing on the latter one. For this, I utilized my lived experience of using the software for the purpose as a practitioner, trainer, and teacher of it as the data. I present the findings under two global themes of modification of the reference types and the APA 7th output style, and the management of sources in the library for the purpose of their accurate citations in word document. On the findings of this study, it has been drawn that the EndNote X9, with slight modification of some of the reference types and the APA 7th output style, creates accurate citations of various sources if we assign the accurate reference types to them and enter the data appropriately in each relevant reference fields in the Endnote library. This paper is expected to be useful to the academic writers for systematizing citation in their work.